Thermal and activation energy of renewable polymer after UV irradiation - Mat Hassan, Nik Normunira; M. Rus, A. Z. (Asian Research Publishing Network (ARPN), 2016)
Renewable polymer made from renewable material is one of the most important group of polymer because of their versatility and they can be manufactured in a wide range of insulation and automotive application. In this project, renewable polymer based on waste vegetable oil were synthesized and crosslink with commercial polymethane polyphenyl isocyanate. The renewable polymer foam was compressed by using hot compression moulding technique at 90 o C based on the evaporation of volatile matter and known as compressed renewable polymer (CRP). The thermal degradation and activation energy of CRP samples is consistant with the increasing of UV irradiation time at the first degradation, second degradation and third degradation. This is due to thermal stability of CRP samples at the hard segment has a great influence on the thermal stability of soft segment. The higher thermal stability of hard segment leads to a higher degradation temperature of soft segment.